PARTISIPASI PRIA DALAM PENGGUNAAN KONTRASEPSI ( ANALISIS SDKI 2012 ) - , Puji Hayuningsih, Dr. Sukamdi.,M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Male participation in contraceptive use in Indonesia is still very low and stagnant. The low participation of men is partly because information about the benefits of male contraception is not widely understood by the public as a whole so that it appears wrong perception of family planning. It is therefore important to determine whether the perception of a significant effect on the participation of men in the use of contraception, including the perception that the dominant influence on male participation in contraceptive use. Research done using secondary data sourced from the Indonesian Demographic and Health Survey (IDHS) in 2012, the research subjects were male mating in Indonesia aged 15-54 years in the analysis is divided into Java Bali, Outer Java Bali I, Outer Java Bali II and Indonesia. The study shows that a better perception toward family planning has a positive impact in increasing male participation in contraceptive use and family planning assumption that men are women's affairs became the dominant influence on the perception of male participation. The study also found that respondent characteristics that influence male participation in contraceptive use is not the same in every region. These conditions indicate that the region is an important factor that must be considered in an effort to increase the participation of men. Meanwhile, knowledge also proved influential on men's participation. However, when knowledge is controlled variables of education, the opportunity to use a male contraceptive has decreased. Based on the results of the study there are two (2) important points to be emphasized in understanding the behavior of male participation in contraceptive use. Firstly, region of residence is an important factor that should not be ignored in understanding the behavior of male participation in contraceptive use. Secondly, education man becomes one of the characteristics of respondents who had a major role in influencing the behavior of male participation. Keyword: Male Participation, Contraception, Perception